Research of financing problems and countermeasures of small and medium enterprises in China - Duan Xuan (2020)
Small and medium-sized enterprises (SMEs) play a very important role in promoting economic growth and increasing employment rates. As China’s economy enters a new normal development stage, SMEs have attracted the attention of all sectors of society. However, the financing difficulty of SMEs has always been a problem on their development path, and throughout the entire life cycle. In recent years, the Chinese government has continuously introduced policies and guidelines to support SMEs, but most of them have achieved little effect.This work starts with a brief introduction, including research background, overall research status, research methods, innovations and deficiencies. Besides, it introduces relevant definitions and the current financing status of SMEs. In addition, it analyzes the root causes of the financing problem from an internal and external perspective and points out that poor management, deficit credit, insufficient financial policy support and legal protection have caused the deterioration of the financing problems. It also analyzes and draws lessons from the advanced financing experiences of some other countries and regions. This research argues that the joint efforts of different parties are beneficial for SMEs financing. Firstly, SMEs should strengthen their own construction, standardize management and improve credit assets. Secondly, the government should introduce preferential policies and constantly enrich the financial system. Thirdly, it should be established an open credit investigation system and sound credit guarantee institutions. Fourthly, financing channels for SMEs should be broaden. Finally, it should be made full use of innovative financing methods and tools.